Human skin-derived ABCB5+ stem cell injection improves liver disease parameters in Mdr2KO mice - Hartwig, Vanessa; Dewidar, Bedair; Lin, Tao; Dropmann, Anne; Ganss, Christoph; Kluth, Mark Andreas; Tappenbeck, Nils; Tietze, Lysann; Christ, Bruno; Frank, Markus; Vogelmann, Roger; Ebert, Matthias; et al. (Archives of toxicology, 2019)
Although liver transplantation is a potential effective cure for patients with end-stage liver diseases, this strategy has several drawbacks including high cost, long waiting list, and limited availability of liver organs. Therefore, stem cell-based therapy is presented as an alternative option, which showed promising results in animal models of acute and chronic liver injuries. ABCB5+ cells isolated from skin dermis represent an easy accessible and expandable source of homogenous stem cell populations. In addition, ABCB5+ cells showed already promising results in the treatment of corneal and skin injury. To date, the effect of these cells on liver injury is still unknown. In the current study, sixteen weeks old Mdr2KO mice were i.v. injected with 500,000 ABCB5+ cells using different experimental setups. The effects of cellular therapy on inflammation, fibrosis, apoptosis, and proliferation were analyzed in the collected liver tissues. Toxicity of ABCB5+ cells was additionally investigated in mice with partial liver resection. In vitro, the fibrosis- and inflammatory-modulating effects of supernatant from ABCB5+ cells were examined in the human hepatic stellate cell line (LX-2). Cell injections into fibrotic Mdr2KO mice as well as into mice upon partial liver resection have no signs of toxicity with regard to cell transformation, cellular damage, fibrosis or inflammation as compared to controls. We next investigated the effects of ABCB5+ cells on established biliary liver fibrosis in the Mdr2KO mice. ABCB5+ cells to some extent influenced the shape of the liver inflammatory response and significantly reduced the amount of collagen deposition, as estimated from quantification of sirius red staining. Furthermore, reduced apoptosis and enhanced death compensatory proliferation resulted from ABCB5+ cell transformation. The stem cells secreted several trophic factors that activated TGF-β family signaling in cultured LX-2 hepatic stellate cells (HSCs), therewith shaping cell fate to an αSMAhigh, Vimentinlow phenotype. Taken together, ABCB5+ cells can represent a safe and feasible strategy to support liver regeneration and to reduce liver fibrosis in chronic liver diseases.
Gesehen am 13.03.2020
Im Titel ist "+" hochgestellt